Effects of Land Uses on Soil Quality of Shwan Sub-basin, Kirkuk Governorate, Northern Iraq - Al-Gburi, Hind Fadhil; Al-Tawash, Balsam Salim; Al–Tamimi, Omer Sabah; Schüth, Christoph (Iraqi Journal of Science, 2023)
Thirty-two soil samples were collected from the study area in October 2020 for geochemical and pollutants investigation of Shwan Sub-basin soil. All soil samples were analysed for different geochemical analyses. The analysis results revealed that the pH values in soil samples ranged from 7.12 to 7.56 with a mean of 7.327. According to the pH values detected in the soil samples, the soil is classified as neutral soil. The electrical conductivity ranged from 0.92 mmhos/cm to 7.8 mmhos/cm with a mean of 1.53 mmhos/cm. Thus, according to the detected electrical conductivity values, the soil was classified as non-saline to slightly saline. The organic matter ranged from 1.14% to 1.45% with a mean value of 1.326 %, while total organic carbon ranged from 0.66 % to 0.84 % with a mean value of 0.769 % which indicated the soil was characterized by low organic content. The results of the geochemical analysis revealed that the major and minor element mean concentrations were in the order Si> Ca> Al> Fe> Mg > K> Ti> Na> P> Mn> S> Cl> N. The average concentrations of trace elements in soil samples followed the decreasing order Sr > Cr> Ba> Zr> Ni> V> Zn> Ta> Rb> Cu> Nb> Y> Pb> Co> Ga> Mo> As> Th> Br> Sn> I. Furthermore, the comparison between heavy metal concentrations in the soil of the study area and metal concentrations in the world soil limit and Indirect Geochemical Background revealed an increase in metal concentrations of Cr, Ni, Zn, Co, As, Mo and Ta. Multivariate statistical analyses, such as Principal Component Analysis and Agglomerative Hierarchal Cluster Analysis, identified the potential sources of pollutants in the soil. Most metals are from natural sources and some of them are from anthropogenic sources mostly from agricultural activities mainly fertilizers use and the waste of animals breeding on farms. Besides industrial activities such as deposits of pollutants from emissions of petroleum refineries located inside or close to the study area. In addition, building blocks and paint factories.